Gold(I) complexes of tetrathiaheterohelicene phosphanes - Cauteruccio, Silvia; Blanco Jaimes, Maria Camila; Rominger, Frank; Prager, Stefan; Dreuw, Andreas; Hashmi, A. Stephen K. (Inorganic chemistry, 2013)
New tetrathia[7]helicene-based (7-TH-based) gold(I) complexes 6 and 7 have been readily prepared by reaction of the respective phosphine ligands 2 and 3 with Au(tht)Cl in a 1:1 and 1:2 molar ratio, respectively. These complexes have been fully characterized by analytical and spectroscopic techniques as well as quantum chemical calculations.
Gesehen am 18.12.2017